'Madman Theory' or 'Persistent Engagement'? The Coherence of US Cyber Strategy under Trump. Issue 3 (3rd July 2022) - Devanny, Joe
Abstract: The Trump administration authorized an assertive cyber strategy of persistent engagement and defending forward. Less a radical break than an evolution, it reflected the impact of bureaucratic politics, emerging theories about cyber competition and arguments about improving the Obama-era strategy. This article employs recent research into "madman tactics" to reject claims that "Madman Theory" improves understanding of persistent engagement. The new strategy was a coherent, albeit bold, response to the operating environment. Under Trump it was undermined by political contingencies. Pursued prudently under Biden, it could yet achieve its objectives: preserving US superiority, promoting stability and security in cyberspace.